Legal Humanism Based on Local Wisdom: Progressive Legal Development Study in Magelang (Pandecta Research Law Journal, 2022)
Legal development aims to realize justice, certainty, and legal benefits, so legal development is explored in the social interaction of society itself. This research is concerned with the development of progressive and humanist law based on local wisdom. The concept looks at the relationship between 1) local wisdom and legal development, 2) local community participation and legal development, and 3) progressive legal development based on local wisdom. The type of juridical sociological research, data collection techniques with documentation, observation, and interviews, then the data analysis technique used is the interaction analysis model. The results of the study are the existence of local wisdom values in influencing the development of law in the community, namely the value of mutual cooperation and the value of deliberation. Community participation in the development of law in society has space for community participation in legal developments since planning, implementation, monitoring and evaluation. The values of local wisdom and community participation have potential in the development of progressive-humanist law, namely in the development of progressive and humanist law influenced by the values of local wisdom and the role of community participation so as to be able to build a law of conscience, respect human dignity and be able to provide a sense of justice according to the noble values that live in society. The suggestion from this research is that the community always maintains and preserves local wisdom that lives and grows in people's lives. The community and local government always maintain a synergistic relationship in the implementation of democratic community participation. In policy planning, it always explores the values of local wisdom in society and always involves community participation in creating progressive and humanist laws.